A deep sequencing reveals significant diversity among dominant variants and evolutionary dynamics of avian leukosis viruses in two infectious ecosystems. Issue 1 (December 2016) - Meng, Fanfeng; Dong, Xuan; Hu, Tao; Chang, Shuang; Fan, Jianhua; Zhao, Peng; Cui, Zhizhong
Abstract Background As a typical retrovirus, the evolution of Avian leukosis virus subgroup J (ALV-J) in different infectious ecosystems is not characterized, what we know is there are a cloud of diverse variants, namely quasispecies with considerable genetic diversity. This study is to explore the selection of infectious ecosystems on dominant variants and their evolutionary dynamics of ALV-J between DF1 cells and specific-pathogen-free (SPF) chickens. High-throughput sequencing platforms provide an approach for detecting quasispecies diversity more fully. Results An average of about 20, 000 valid reads were obtained from two variable regions ofgp85 gene andLTR-U3 region from each sample in different infectious ecosystems. The top 10 dominant variants among ALV-J from chicken plasmas, DF1 cells and liver tumor were completely different from each other. Also there was a difference of shannon entropy and global selection pressure values (ω) in different infectious ecosystems. In the plasmas of two chickens, a large portion of quasispecies contained a 3-peptides "LSD" repeat insertion that was only less than 0.01% in DF1 cell culture supernatants. In parallel studies, theLTR-U3 region of ALV-J from the chicken plasmas demonstrated more variants with mutations in their transcription regulatory elements than those from DF1 cells. Conclusions Our data taken together suggest that the molecular epidemiology based on isolated ALV-J in cell culture may not represent the true evolution of virus in chicken flocks in the field. The biological significance of the "LSD" insert and mutations inLTR-U3 needs to be further studied.